2012
DOI: 10.1136/emermed-2012-201760
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate and systolic blood pressure in patients with minor to moderate, non-haemorrhagic injury versus normal controls

Abstract: Median HR remained approximately 10 bpm higher in the TARN (injury) set compared to the HSE (non-injury, control) set, irrespective of age. Understanding that HR reacts in this way for mild to moderately injured patients is important as it will affect clinical interpretation during the initial assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This study showed that the SBP was significantly higher at ED triage rather than during ambulance transport. As other causes that could influence vital signs were largely controlled for, and immobilization has been shown not to affect vital signs [10], the increase observed in minimally injured individuals at ED triage was likely because of mild anxiety (or a relative whitecoat effect). An explanation for this finding may relate to the fact that the moderately injured individuals in the ankle/wrist fracture group suffered greater tissue injury than the individuals with neck sprain.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the SBP was significantly higher at ED triage rather than during ambulance transport. As other causes that could influence vital signs were largely controlled for, and immobilization has been shown not to affect vital signs [10], the increase observed in minimally injured individuals at ED triage was likely because of mild anxiety (or a relative whitecoat effect). An explanation for this finding may relate to the fact that the moderately injured individuals in the ankle/wrist fracture group suffered greater tissue injury than the individuals with neck sprain.…”
Section: Discussionmentioning
confidence: 99%
“…Several tools have been developed to identify the cohort of patients that will benefit from this resuscitation strategy but none have proved superior to experienced clinician judgement (McLaughlin et al., 2008; Schreiber et al., 2007; Yucel et al., 2006). Physiological parameters previously advocated for quantifying blood loss and grading shock severity have been found to be insensitive, with patients frequently maintaining normal physiology despite losing up to 40% of their circulating volume (Bruijns et al., 2012; Eastridge et al., 2007). A pragmatic approach is to use initial blood product-based resuscitation in patients whom the trauma team identifies as likely to require 4 or more units of packed red cells in the first 4 h of resuscitation, or greater than one circulating volume in the first 24 h.…”
Section: Haemostatic Resuscitationmentioning
confidence: 99%